2018
DOI: 10.3390/v10060328
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Analysis of Two Novel Type 2 Porcine Reproductive and Respiratory Syndrome Viruses with Complex Genome Recombination between Lineage 8, 3, and 1 Strains Identified in Southwestern China

Abstract: Recombination among porcine reproductive and respiratory syndrome viruses (PRRSVs) is thought to contribute to the emergence of new PRRSV variants. In this study, two newly emerged PRRSV strains, designated SCcd16 and SCya17, are isolated from lung tissues of piglets in Southwestern China. Genome comparative analysis reveals that SCcd16/SCya17 exhibit 93.1%/93.2%, 86.9%/87.0%, 85.3%/85.7%, and 83.6%/82.0% nucleotide similarity to PRRSVs JXA1, VR-2332, QYYZ and NADC30, respectively. They only exhibit 44.8%/45.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…Subsequently, lineage 3 PRRSV emerged in Hong Kong (2004) and mainland China (2005). However, the reemerged lineage 3 PRRSV strains in southern China display increased genetic diversity (Brar et al, ; Dong et al, ; Gao et al, ; Liu et al, ; Lu et al, ; Shi et al, ; Sun et al, ; Zhou et al, ). In this study, SD110‐1608 and SDWH27‐1710 were classified into sublineage 3.5 and maintained a close relationship with representative strains QYYZ and GDsg, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, lineage 3 PRRSV emerged in Hong Kong (2004) and mainland China (2005). However, the reemerged lineage 3 PRRSV strains in southern China display increased genetic diversity (Brar et al, ; Dong et al, ; Gao et al, ; Liu et al, ; Lu et al, ; Shi et al, ; Sun et al, ; Zhou et al, ). In this study, SD110‐1608 and SDWH27‐1710 were classified into sublineage 3.5 and maintained a close relationship with representative strains QYYZ and GDsg, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Lineage 3 has widely spread throughout Guangdong Province (Gao et al, ; Xie et al, ). Consequently, lineage 3 strains have been constantly detected in neighbouring provinces in southern China (Liu et al, ; Zhou et al, ). Considering the collected data, analysed phylogenies, geographic distribution and circulation of pigs in the swine trade, the hypothesized transmission route is that the disease was initially transmitted to the peripheral provinces (Gao et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the complex recombination pattern among a NADC30-like, a JXA1-like, and the classical PRRSV-2-derived MLV vaccine strain (RespPRRS MLV) has never been described. In our previous investigation, we found that JXA1-like, NADC30-like, VR-2332-like, and QYYZ-like strains had coexisted in some pig herds in the Sichuan Province since 2016, and the following different recombination patterns were observed in this region: (i) NADC30-like + JXA1-like [ 23 ]; (ii)NADC30-like + JXA1-like + VR-2332-like [ 27 ]; and (iii) NADC30-like + JXA1-like + QYYZ-like [ 28 ]. This evidence thus further supported the possible recombination among the PRRSV strains, NADC30-like and JXA1-like, and the vaccine strain, RespPRRS MLV (VR-2332-like).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NADC30-like strains were found to recombine with JXA1-like strains (HENAN-HEB, JL580, FJ1402, TJnh1501, 15HEN1, HNhx, and SCnj16) [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ] or VR-2332-like strains (Chsx1401, HENAN-XINX, and HNyc15) [ 14 , 20 , 24 ]. Moreover, several complex recombinants among the three lineages of PRRSV-2 strains (SDhz1512, SD17-38, SCcd16, SCcd17, and SCya17) have also been observed in China [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing diversity of the type 2 PRRSV is related to point mutations and genetic recombination among the field strains or in between the field and modified live vaccine (MLV) strains, which can lead to some new emerging antigenic variant strains ( 6 , 18 24 ). In the present study, we identify two novel recombinant PRRSV strains circulating in swine farms in Guangxi, a province of southern China.…”
Section: Introductionmentioning
confidence: 99%